Instrumental neutron activation analysis of marine sediment in-house reference material - Nazaratul Ashifa, Abdullah Salim; Mohd Suhaimi, Hamzah; Md Suhaimi, Elias; Wee, Boon Siong; Shamsiah, Ab Rahman; Aziah, Hashim; Shakirah, Shukor (Malaysian Nuclear Society, 2013)
Reference materials play an important role in demonstrating the quality and reliability of analytical data. The advantage of using in-house reference materials is that they provide a relatively cheap option as compared to using commercially available certified reference material (CRM) and can closely resemble the routine test sample. A marine sediment sample was designed as an in-house reference material, in the framework of quality assurance and control (QA/QC) program of the Neutron Activation Analysis (NAA) Laboratory at Nuclear Malaysia. The NAA technique was solely used for the homogeneity test of the marine sediment sample. The CRM of IAEA- Soil 7 and IAEA- SL1 (Lake Sediment) were applied in the analysis as compatible matrixbased reference materials for QA purposes.